Analysis and design of a SiGe-HBT based terahertz detector for imaging arrays applications. (August 2019) - Ghodsi, Hamed; Kaatuzian, Hassan
Abstract: In this paper, we will introduce a new designed direct conversion terahertz detector. Characteristics of this new detector have been compared with a prefabricated design in order to obtain better performance of our new proposed design. We have introduced an exponentially graded base SiGe-HBT instead of linearly graded ones, and have used a single transistor with two base contacts, which is equivalent to two transistors in common emitter configuration. New proposed detector has been analyzed by both compact circuit and two dimensional carrier transport models. Responsivity and minimum noise equivalent power of new detector are about 4.9 A/W and 6.5 pW/Hz 1/2 at 700 GHz respectively, while these characteristics for the prefabricated detector, are about 1 A/W and 50 pW/Hz 1/2 . Also about 231μW/pixel decrement in power consumption for the same responsivity, and a same bandwidth have been achieved.